Coronavirus Disease 2019 (COVID-19) and Pregnancy: Combating Isolation to Improve Outcomes. Issue 1 (July 2020) - Jago, Caitlin Anne; Singh, Sukhbir Sony; Moretti, Felipe
Abstract : With the current global coronavirus disease 2019 (COVID-19) pandemic, new challenges arise as social distancing and isolation have become the standard for safety. Evidence supports the protective benefits of social connections and support during pregnancy and labor; there are increased maternal, fetal, and pregnancy risks when pregnant and laboring women lack support. As health care professionals take appropriate precautions to protect patients and themselves from infection, there must be a balance to ensure that we do not neglect the importance of social and emotional support during important milestones such as pregnancy and childbirth. Resources are available to help pregnant women, and technology represents an opportunity for innovation in providing care. Abstract : Evidence supports protective benefits of social support during pregnancy and labor; lack of support increases maternal, fetal, and pregnancy risks.